2009
DOI: 10.1159/000246573
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Diagnostic Tests and Therapies for Dry Eye Disease

Abstract: Aim: The purpose of this study was to survey the attitudes of optometrists and ophthalmologists, located in a number of different countries, towards diagnostic tests and therapies for dry eye disease. Methods: A web-based questionnaire was used to survey attitudes using forced-choice questions and Likert scales. Results: Sixty-one respondents (23 ophthalmologists and 38 optometrists) reported a wide range of patient dry eye symptoms. A large variation in use of diagnostic tests was noted. Patient symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
3
25
0
3
Order By: Relevance
“…The strong preference to use TBUT with fluorescein is in agreement with previous studies 7Y10 ; although this technique is easily performed and commonly applied, fluorescein destabilizes the tear film. 7,11 That more than 90% of respondents indicated that they routinely evaluate MGs may reflect the influence of the recent commercial availability of lipid replacement artificial tears and/or increased awareness of the importance of MG abnormalities in dry eye subsequent to the publication of the findings from the International Workshop on MGD. 29 Interestingly, optometrists who nominated an interest in dry eye disease tended to use the noninvasive observation of interference fringes more frequently than nonspecialist practitioners; this difference may reflect an enhanced understanding of fluorescein's limitations by this subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong preference to use TBUT with fluorescein is in agreement with previous studies 7Y10 ; although this technique is easily performed and commonly applied, fluorescein destabilizes the tear film. 7,11 That more than 90% of respondents indicated that they routinely evaluate MGs may reflect the influence of the recent commercial availability of lipid replacement artificial tears and/or increased awareness of the importance of MG abnormalities in dry eye subsequent to the publication of the findings from the International Workshop on MGD. 29 Interestingly, optometrists who nominated an interest in dry eye disease tended to use the noninvasive observation of interference fringes more frequently than nonspecialist practitioners; this difference may reflect an enhanced understanding of fluorescein's limitations by this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these previous surveys suffered from a low response rate 9,11 and/or were restricted to the sampling of internationally renowned experts in dry eye 7,10 and are therefore not likely to be representative of the general practice behaviors of optometrists. Only one study considered practitioner preferences for dry eye treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have sought to evaluate the self‐reported dry eye clinical practices of eye care providers. Together, these studies indicate for significant variations in clinical diagnostic approaches, with preferences for examination techniques being influenced by factors such as the health profession (optometrist vs ophthalmologist) and demographic (region of the world) of the survey population . The majority of these studies were, however, undertaken prior to the DEWS systematic reviews, which were integral for achieving international consensus to both define the disease and outline protocols for clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…show the highest sensitivity and specificity for dry eye diagnosis supported with diagnostic 402 tests [3], [9], [13], [14], [22]. In this investigation no specific questionnaire was used for DED, 403 and the optometrists often used personally designed questionnaires.…”
mentioning
confidence: 99%